Evaluation of the Adhesion between Overlays and Substrates in Concrete Floors: Literature Survey, Recent Non-Destructive and Semi-Destructive Testing Methods, and Research Gaps - Szymanowski, Jacek (Buildings (Basel), 2019)
Non-destructive testing (NDT) and semi-destructive testing (SDT) have recently been more frequently used for the evaluation and condition assessment of concrete floors in various types of buildings. The subject of the article is to briefly introduce the reader to the problem of adhesion between overlays and substrates in concrete floors and to illustrate the current state of knowledge on the subject. The aim of this paper was to briefly describe the recently used non-destructive and semi-destructive testing methods and the parameters useful for characterizing the adhesion between overlays and substrates in concrete floors, as well as the methods useful to characterize the functional properties of the overlays. A recent literature survey, related to the adhesion between the overlays and substrates in concrete floors, is thus shown. Special emphasis was placed on the critical review of the current research results. Based on the analysis of the literature review, research gaps have been presented in order to highlight future research directions.